2017
DOI: 10.1002/jaba.385
|View full text |Cite
|
Sign up to set email alerts
|

Improving the interview skills of college students using behavioral skills training

Abstract: Obtaining a job as a college graduate is partly dependent on interview performance. We used a multiple baseline design across skills to evaluate the effects of behavioral skills training with self-evaluation for five college students. Training effects were evaluated using simulated interviews as baseline and posttraining assessments. All participants acquired targeted skills, but we observed some individual differences. Participants were satisfied with training outcomes and rated the procedures as acceptable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…The training time included the BST session that was required for all participants to meet the mastery criterion. Stocco et al (2017) evaluated the effects of BST with self-evaluation to teach interview skills to typically developing college students. Results showed that as a result of this training, participants acquired the target skills of answering interview questions appropriately, smiling and appropriate posture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The training time included the BST session that was required for all participants to meet the mastery criterion. Stocco et al (2017) evaluated the effects of BST with self-evaluation to teach interview skills to typically developing college students. Results showed that as a result of this training, participants acquired the target skills of answering interview questions appropriately, smiling and appropriate posture.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot make any claims regarding the performance of typically developing students with the same training program components. Future work in this area should compare performance of typically developing young adults with adults with ASD to observe potential differences (Stocco et al, 2017). Although interview skills are important amongst all populations, information on training methods to improve interview responses for adults with ASD is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They help students enter conversations without the expectation that they will receive a job offer or an internship. Stocco, Thompson, Hart, and Soriano (2017) incorporated behavioral skills training (BST)-instruct, model, practice, and provide feedback-in their individualized mock interviews. These personalized training lessons included reflective sessions for students to assess training received and post-interview evaluation.…”
Section: Mock and Simulated Interview Trainingmentioning
confidence: 99%
“…Behavioral skills training (BST) is a training package composed of instructions, modeling, and rehearsal with performance feedback. BST has been used to teach a range of skills to a variety of learners, including safety skills to children and adults (Johnson et al, 2005;Komaki, Heinzmann, & Lawson, 1980;Miltenberger et al, 2004), therapy provision skills to graduate student counselors (Hassan, Thomson, Khan, Burnham Riosa, & Weiss, 2017), interview skills to college students (Stocco, Thompson, Hart, & Soriano, 2017), staff training skills to supervisors (Parsons, Rollyson, & Reid, 2013), behavior management skills to staff working with individuals with disabilities (Belisle, Rowsey, & Dixon, 2016;Sarakoff & Sturmey, 2004), and child management skills to parents (Drifke, Tiger, & Wierzba, 2017;Feldman, Case, Rincover, Towns, & Betel, 1989). Although component analyses of BST have indicated that modeling and/or rehearsal with feedback are the BST components most likely to be correlated with significant improvements in performance (Komaki et al, 1980;Krumhus & Malott, 1980;Shapiro & Kazemi, 2017;Ward-Horner & Sturmey, 2012), there are no studies that have assessed the efficacy of each BST component independent of the effects of instructions.…”
mentioning
confidence: 99%